2019
DOI: 10.3791/59637
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Wireless Video-EEG System to Monitor Epileptiform Discharges Following Lateral Fluid-Percussion Induced Traumatic Brain Injury

Abstract: The lateral fluid percussion injury (FPI) model is well established and has been used to study TBI and post-traumatic epilepsy (PTE). However, considerable variability has been reported for the specific parameters used in different studies that have employed this model, making it difficult to harmonize and interpret the results between laboratories. For example, variability has been reported regarding the size and location of the craniectomy, how the Luer lock hub is placed relative to the craniectomy, the atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, rats with clinically relevant mutations have also been studied ( Ohmori et al, 2020 ). Diverse EEG setups have been developed for both tethered ( Medlej et al, 2019 ) and wireless ( McGuire et al, 2019 ) EEG in rats, and ex vivo brain slice preparations can be used to study seizure susceptibility ( Accardi et al, 2018 ) and epileptogenesis ( Dyhrfjeld-Johnsen et al, 2010 ), and to screen ASDs ( Hill et al, 2010 ).…”
Section: Introduction: What Is Epilepsy?mentioning
confidence: 99%
“…However, rats with clinically relevant mutations have also been studied ( Ohmori et al, 2020 ). Diverse EEG setups have been developed for both tethered ( Medlej et al, 2019 ) and wireless ( McGuire et al, 2019 ) EEG in rats, and ex vivo brain slice preparations can be used to study seizure susceptibility ( Accardi et al, 2018 ) and epileptogenesis ( Dyhrfjeld-Johnsen et al, 2010 ), and to screen ASDs ( Hill et al, 2010 ).…”
Section: Introduction: What Is Epilepsy?mentioning
confidence: 99%
“…Progression of epilepsy often leads to brain dysfunction, limb convulsions, and behavioural disorders or sensory disturbances, which seriously disturb patients • 651 [21,22]. According to the literature, development of epilepsy is known to result in the increase of oxidative stress, which leads to excessive neurotransmitter excitation, neuronal apoptosis or metabolic structural damage [23,24]. The present study found that Cu-Zn SOD suppresses epilepsy and alters the NaV1.2/Nrf2/ HO-1 axis.…”
Section: Discussionmentioning
confidence: 59%
“…Adult, male, Wistar rats (300-350g) were obtained from Charles River Laboratories (Wilmington, MA) and single housed in a 12-hour light/dark schedule with ad libitum access to food and water. The lateral fluid percussion injury procedure was performed as we have previously published (McGuire et al, 2019).…”
Section: Tbi Proceduresmentioning
confidence: 99%